Research on the dynamic co-evolution of the complex system of economy-innovation-environment of the marine industry in China - Qirong, Wang; Jingrong, Xu; Yang, Zhang (Frontiers in Marine Science, 2023)
In the context of accelerating the construction of a marine power, relying on scientific and technological innovation to drive the high-quality growth of the marine economy and paying attention to the protection of the marine ecological environment are the strategic requirements for promoting the sustainable development of the marine industry in China. This paper describes the development of marine industry as a complex system of marine economy-innovation-environment, that is, it describes the marine economy, marine innovation and marine environment as a complex system that interacts and restricts each other. Based on the theory of synergetics, a dynamic co-evolution model of the complex system of marine economy-innovation-environment is constructed, and the accelerating genetic algorithm is used to solve the model, so that the contribution degree of each subsystem and interaction effect between them are calculated. This paper uses this model to conduct an empirical study on the current situation of co-evolution of the complex system of marine economy-innovationenvironment from 2003 to 2019 in China. The research results show that: (1) The order degree of the systems of economy, innovation and environment of the marine industry in China is on the rise; (2) At present, the systems of innovation and environment of the marine industry in China are in an evolutionary state, while the system of economy is showing a "recession" trend; (3) There are competition and cooperation between the system of economy-innovation-environment of the marine industry in China at the same time. The system of economy-environment is in a lose-lose state. The system of economy and innovation and the system of innovation and environment are in a win-lose complementary relationship. This result is conducive to the current transformation and development of China's marine industry, adjusting the direction of marine science and technology inputs, optimizing the structure of marine science and technology outputs, enhancing the coordinated development level of regional and even national marine systems, and providing policy reference for promoting multiobjective collaborative governance in marine management department and accelerating the process of high-quality marine development.